Analysis of Factors Causing Learning Difficulties in High School Students on the Excretion System Material - Faruq, Hilman (BIOEDUSCIENCE, 2025)
Background: Learning difficulties related to the human excretory system remain a persistent challenge in high school biology education, particularly concerning abstract subtopics such as urine formation, nephron structures, and physiological mechanisms including filtration, reabsorption, and secretion. This study aims to identify internal and external factors that hinder student understanding of these concepts. Methods: A descriptive approach was employed, involving the distribution of structured questionnaires to 73 high school students. The instruments were designed to assess both cognitive and instructional aspects influencing learning barriers. Data analysis focused on patterns of student responses concerning content difficulty, teaching methods, and availability of learning resources. Results: The study revealed that 85.7% of students encountered substantial difficulty in understanding urine formation within the nephron. Additionally, 77.1% reported that monotonous, teacher-centered instruction contributed to their challenges, while 65.7% cited a lack of practical laboratory experiences. Cognitive issues such as low abstract reasoning ability, poor visualization skills, limited memory retention, and low motivation were identified as core barriers. Instructional deficiencies, including minimal use of multimedia and interactive strategies, further exacerbated learning difficulties. Conclusions: The results highlight the importance of integrating visual aids, interactive media, and experiential learning in biology instruction to improve conceptual understanding. Addressing both cognitive and instructional barriers is essential for enhancing learning outcomes in complex biological systems.